Inhibition of the STAT3/Fanconi anemia axis is synthetic lethal with PARP inhibition in breast cancer - Celia D. Rouault; Lucile Bansard; Elena Martínez-Balsalobre; Caroline Bonnet; Julien Wicinski; Shuheng Lin; Ludovic Colombeau; Sylvain Debieu; Guillaume Pinna; Marie Vandamme; Margot Machu; Olivier Rosnet; et al. (Nature Communications)
Abstract The targeting of cancer stem cells (CSCs) has proven to be an effective approach for limiting tumor progression, thus necessitating the identification of new drugs with anti-CSC activity. Through a high-throughput drug repositioning screen, we identify the antibiotic Nifuroxazide (NIF) as a potent anti-CSC compound. Utilizing a click chemistry strategy, we demonstrate that NIF is a prodrug that is specifically bioactivated in breast CSCs. Mechanistically, NIF-induced CSC death is a result of a synergistic action that combines the generation of DNA interstrand crosslinks with the inhibition of the Fanconi anemia (FA) pathway activity. NIF treatment mimics FA-deficiency through the inhibition of STAT3, which we identify as a non-canonical transcription factor of FA-related genes. NIF induces a chemical HRDness (Homologous Recombination Deficiency) in CSCs that (re)sensitizes breast cancers with innate or acquired resistance to PARP inhibitor (PARPi) in patient-derived xenograft models. Our results suggest that NIF may be useful in combination with PARPi for the treatment of breast tumors, regardless of their HRD status.